The New Parapolice : Risk Markets and Commodified Social Control - Rigakos, George (Book collections on Project MUSE., 2002)
Rigakos argues that for-profit policing and security companies adopt many of the tactics and functions of the public police, and are less distinguishable from the latter than has been previously assumed in the criminological literature.